Penggunaan Shuujoshi Ne, Wa, dan Kana Dalam Drama Dragon Zakura 2 - Aini, Alfina Nur; Indrowaty, Sri Aju (Jurnal Pendidikan Bahasa Jepang Undiksha, 2024)
Shuujoshi is a particle located at the end of a sentence. The purpose of this research is to find out what are the functions of shuujoshi ne, wa, and kana in Dragon Zakura 2 drama. This research uses qualitative methods with a descriptive approach. Based on the results of the study, there are 234 sentences containing shuujoshi ne, wa, kana in Dragon Zakura 2 drama. From 234 sentences, the researcher only analyzed 10 sentences, including 5 shuujoshi ne, 2 shuujoshi wa, and 3 shuujoshi kana. Shuujoshi ne serves to express agreement with the interlocutor; ask to get reassurance from the interlocutor; express awe, disappointment, surprise, etc.; subtly show requests to the interlocutor; and express an opinion. Shuujoshi wa serves to refine speech in a statement and express admiration, disappointment, surrender, etc. Shuujoshi kana serves to express expectations or supplications indirectly, show uncertainty or doubt, and ask something to the interlocutor.